General Framework of Fault-based Liability and Reasonability of Its Modiϐication upon Covering of Injuries, Stemming from Labour-Law Relationship - Matcharadze, Miranda (Journal of Law, 2017)
The Labour Code of Georgia does not provide for some special rule regarding damages in labour law context. The procedure of coverage of injuries arising from employment relationships is regulated by Georgia law. The article discusses specificities of fault upon coverage of injuries arising from employment relationships. In general, what is typical for fault, as one of the grounds of liability in labour disputes. Specifically, against a backdrop of subordination principle, modification of fault in employment relationships often results in different legal consequences in the context of damages.